Customer co-creation in B2C e-commerce: does it lead to better new products? - Pee, Loo Geok (2016)
The business-to-consumer e-commerce platform facilitates direct reach to customers and is especially conducive to large-scale customer co-creation. Many major e-commerce businesses have begun to leverage the platform to co-create with customers in new product development (NPD), in anticipation of new products that are more innovative and sell better. Yet, empirical evidence for the impact of customer co-creation is still scarce. This study investigates the impact by distinguishing among different co-creation tasks (idea co-creation and decision co-creation) and NPD stages (product design and commercialization). Based on the co-creation and innovation literature, it is hypothesized that idea co-creation has a stronger impact when there is also decision co-creation. Further, co-creation in the product design stage is expected to have a stronger effect on product innovativeness, while co-creation in the commercialization stage has a stronger effect on product sales. The hypotheses were tested with data on 107 actual products. Looking beyond a homogenous conceptualization of co-creation enhances our understanding of how it influences different aspects of new product success. This is also one of the earliest studies to report empirical evidence for the impact of customer co-creation in e-commerce. The findings offer specific insights into the co-creation tasks and NPD stages to open for customer co-creation in practice.